Riding the Indian tiger : understanding India--the world's fastest growing market - Nobrega, William, 1961-; Sinha, Ashish, 1970- (Hoboken, N.J. : J. Wiley & Sons, 2008)
In 2008, India will likely overtake China as the world's fastest growing economy and become one of the largest economies globally. Foreign investment is increasing dramatically and business opportunities abound for those who know how to find them. W.
The largest market the world has ever seen -- Bulls & bears in Mumbai : India's financial markets -- Why India will outperform China -- The road less traveled : India's infrastructure opportunity -- The next wave : beyond IT & outsourcing -- Look before you leap -- Understanding the Indian business culture.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
John Wiley and Sons
Keywords: Capital market -- India; Investments, Foreign -- India; India -- Economic policy -- 1991-2016.; z; z; Inde -- y; POLITICAL SCIENCE -- Economic Conditions; BUSINESS & ECONOMICS -- Economics -- Comparative; BUSINESS & ECONOMICS -- Economic Conditions; BUSINESS & ECONOMICS -- Economic History; Capital market; Economic policy; Investments, Foreign; India; 83.30 economic conditions, development and structure: general; India; India; 1991-2016; dissertations; Academic theses; Academic theses; 2